2017
DOI: 10.1111/joic.12409
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of Impella use in all‐comers: 1‐year outcomes

Abstract: For patients with need for an Impella device, regardless of the indication, early implantation is associated with better in-hospital and 1-year outcomes as compared to when the device is implanted late as a bailout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…This data also suggests that planned MA‐TMS device insertion concomitantly with CABG as a prophylactic therapy, rather than in response to signs of PCCS, is advantageous. This experience is consistent with a recent study of 262 patients who received percutaneous MA‐TMS devices, which demonstrated that early MA‐TMS device insertion is associated with better in‐hospital and 1‐year outcomes compared to late “bailout” insertion …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This data also suggests that planned MA‐TMS device insertion concomitantly with CABG as a prophylactic therapy, rather than in response to signs of PCCS, is advantageous. This experience is consistent with a recent study of 262 patients who received percutaneous MA‐TMS devices, which demonstrated that early MA‐TMS device insertion is associated with better in‐hospital and 1‐year outcomes compared to late “bailout” insertion …”
Section: Discussionsupporting
confidence: 90%
“…insertion. 4 The results of this series must be considered in light of other studies evaluating high-risk cardiac surgery, especially in the current era of mechanical circulatory support. Discerning which patients will recover and which will require a durable VAD or heart transplantation will allow us to select the right therapy for the right patient.…”
Section: Resultsmentioning
confidence: 98%
“…In terms of the timing of support, several studies suggest that early implantation of a mechanical assist device would improve survival [30][31][32]. Recent extensive animal studies showed that mechanical unloading of the left ventricle before coronary reperfusion limits the expression of proteolytic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…[54][55][56][57][58][59] More recently, small single-centre studies (most notably the Detroit Cardiogenic Shock Initiative), international registry data and our own local experience lend some support to the immediate haemodynamic and potential short-term clinical survival benefits of initiation of percutaneous axial flow LV to aorta support as soon as possible after the onset of shock. 36,56,[60][61][62][63][64][65][66] Other investigations, such as the recent IMPella versus IABP Reduces mortality in STEMI patients treated with primary PCI (IMPRESS) trial, suggest that the benefits of percutaneous MCS devices are time-dependent and unlikely to impact outcomes if employed late, once overt multiorgan dysfunction has occurred. 67…”
mentioning
confidence: 99%